Determinants of Erythrocyte Hydration In Current Opinion in Hematology - Rinehart, Jesse (2010)
PURPOSE OF REVIEW: Maintenance of cellular water and solute homeostasis is critical for survival of the erythrocyte. Inherited or acquired disorders that perturb this homeostasis jeopardize the erythrocyte, leading to its premature destruction. This report reviews recent progress in our understanding the determinants of erythrocyte hydration and its related disorders. RECENT FINDINGS: The molecular and genetic bases of primary disorders of erythrocyte hydration are poorly understood. Recent studies have implicated roles for the anion transporter, SLC4A1, and the Rh-associated glycoprotein, RhAG. The most common secondary disorder associated with perturbed hydration of the erythrocyte is sickle cell disease, where dehydration contributes to disease pathology and clinical complications. Advances in understanding the mechanisms regulating erythrocyte solute and water content, particularly associated with KCl cotransport and Gardos channel activation, have revealed novel signaling mechanisms controlling erythrocyte hydration. These signaling pathways may provide innovative strategies to prevent erythrocyte dehydration in sickle cell disease. SUMMARY: Clinical, translational and biologic studies all contribute to our knowledge of erythrocyte hydration. Understanding the mechanisms controlling erythrocyte water and solute homeostasis will serve as a paradigm for other cells and may reveal new therapeutic targets for disease prevention and treatment.